2012
DOI: 10.1091/mbc.e11-11-0933
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of the preprotein translocase of the outer mitochondrial membrane: protein kinase A phosphorylates the precursor of Tom40 and impairs its import

Abstract: The preprotein translocase of the outer mitochondrial membrane (TOM) functions as the main entry gate for the import of nuclear-encoded proteins into mitochondria. The major subunits of the TOM complex are the three receptors Tom20, Tom22, and Tom70 and the central channel-forming protein Tom40. Cytosolic kinases have been shown to regulate the biogenesis and activity of the Tom receptors. Casein kinase 2 stimulates the biogenesis of Tom22 and Tom20, whereas protein kinase A (PKA) impairs the receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 91 publications
(164 reference statements)
1
66
0
2
Order By: Relevance
“…Moreover, several studies have reported the mitochondrial localization of both soluble adenylyl cyclase and PKA, the latter of which has been demonstrated to phosphorylate and regulate the activity of a number of mitochondrial proteins such as cytochrome c oxidase (1,80,110,113,125). However, it still remains to be established whether activation or inhibition of CB1R-directed signaling promotes alterations in mitochondrial oxidative metabolism through either the suppression or the enhancement of PKAdirected signaling within mitochondria, respectively.…”
Section: The Ecs-mitochondrial Axis: Mechanistic Insightsmentioning
confidence: 99%
“…Moreover, several studies have reported the mitochondrial localization of both soluble adenylyl cyclase and PKA, the latter of which has been demonstrated to phosphorylate and regulate the activity of a number of mitochondrial proteins such as cytochrome c oxidase (1,80,110,113,125). However, it still remains to be established whether activation or inhibition of CB1R-directed signaling promotes alterations in mitochondrial oxidative metabolism through either the suppression or the enhancement of PKAdirected signaling within mitochondria, respectively.…”
Section: The Ecs-mitochondrial Axis: Mechanistic Insightsmentioning
confidence: 99%
“…Protein kinase A (PKA) phosphorylates Tom70 leading to inhibition of the receptor and ultimately impaired delivery of Tom70-dependent substrates into mitochondria. Conversely, the assembly of the TOM complex itself is positively regulated by the action of casein kinase 2 (CK2), by the direct action of this kinase on the central receptor, Tom22 (8,9). These examples demonstrate that mitochondrial translocases are targets of intracellular signaling and that the transport of mitochondrial proteins is integrated into the regulatory circuits that determine the fate and physiology of the cell.…”
Section: Influx Of Proteins Into Mitochondriamentioning
confidence: 99%
“…Several distinguishing features of C. albicans also were observed, e.g., in respect to the TOM complex: C. albicans has no Tom70 and has extensions to the cytosolic domains of Tom6 and Tom7 (Table S1). With recent studies in S. cerevisiae showing that phosphorylation in the cytosolic domains of TOM subunits is crucial for regulation of TOM complex activity in response to changes in metabolic activity (5,6), future analysis of sequence variations in S. cerevisiae and C. albicans could help show how these phosphorylation sites affect cell cycle and metabolism. In some cases hidden Markov models (HMM) proved essential for identifying homologs; for example, an ORF encoding a Tom5-related sequence previously had been unidentified and unannotated because of its small size and sequence divergence.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work in the model yeast Saccharomyces cerevisiae has shown that phosphorylation of specific subunits of the TOM complex regulates the activity of the protein import channel. An elegant coordination of mitochondrial biogenesis with cellular metabolic needs was seen when glucose levels were high, with phosphorylation of TOM complex subunits coinciding with repression of mitochondrial activity (5,6). S. cerevisiae responds to the presence of glucose through metabolic cycling, oscillating cycles of aerobic respiration and glycolytic activity.…”
mentioning
confidence: 99%